Warna Lokal Minangkabau dalam Novel Dayon Karya Akmal Nasery Basral - Intan Ayu Lestari; Ferina Meliasanti; Imam Muhtarom (Departement of Mathematics Education, 2023)
Local colors have an influence on the development and introduction of the local culture of an area. The purpose of the study describes the local colors of Minangkabau in the novel Dayon by Akmal N Basral. Data collection techniques include reading techniques, note-taking techniques, and library techniques. The collected research data is analyzed through three stages including, data reduction, data presentation, and drawing conclusions. The results of the analysis show that there is a local color content in the novel Dayon by Akmal N Basral, including: a) Inyiak Tiger Beliefs, b) Minangkabau Community Customs, c) art, d) language, e) livelihood of foodstuffs, f) local animals, and g) Traditional Houses. The existence of local color content in Dayon's novel shows that the author photographed the activities of the Minangkabau people. The local content is able to become a characteristic of regional communities and is useful in shaping the character of the nation.